Matching-to-sample performance is better analyzed in terms of a four-term contingency than in terms of a three-term contingency. - Jones, Brent; Elliffe, D. (Wiley-Blackwell Publishing, Inc., 2013)
Four pigeons performed a simultaneous matching-to-sample (MTS) task involving two samples and two comparisons that differed in their pixel density and luminance. After a long history of reinforcers for correct responses after both samples, 15 conditions arranged either continuous reinforcement of correct responses after Sample 1 and extinction for all responses after Sample 2, or vice versa. The sample after which correct responses were reinforced alternated across successive conditions. The disparity between the samples and the disparity between the comparisons were varied independently across conditions in a quasifactorial design. Contrary to predictions of extant quantitative models, which assume that MTS tasks involve two 3-term contingencies of reinforcement, matching accuracies were not at chance levels in these conditions, comparison–selection ratios differed after the two samples, and effects on matching accuracies of both sample disparity and comparison disparity were observed. These results were, however, consistent with ordinal and sometimes quantitative predictions of Jones' (2003) theory of stimulus and reinforcement effects in MTS tasks. This theory asserts that MTS tasks involve four-term contingencies of reinforcement and that any tendency to select one comparison more often than the other over a set of trials reflects meaningful differences between comparison-discrimination accuracies after the two samples.